Properties of immobilized candida antarctica lipase B on highly macroporous copolymer - Nurrahmi Handayani,; Nemanja Miletic,; Katja Loos,; Sadijah Achmad,; Bumbun Bundjali, (Universiti Kebangsaan Malaysia, 2011)
In spite of their excellent catalytic properties, enzymes should be improved before their implementation both in industrial and laboratorium scales. Immobilization of enzyme is one of the ways to improve their properties. Candida antarctica lipase B (Cal-B) has been reported in numerous publications to be a particularly useful enzyme catalizing in many type of reaction including regio- and enantio- synthesis. For this case, cross-linking of immobilized Cal-B with 1,2,7,8 diepoxy octane is one of methods that proved significantly more stable from denaturation by heat, organic solvents, and proteolysis than lyophilized powder or soluble enzymes. More over, the aim of this procedure is to improve the activity and reusability of lipase. Enzyme kinetics test was carried out by transesterification reaction between 4-nitrophenyl acetate (pNPA) and methanol by varying substrate concentrations, and the result is immobilized enzymes follows the Michaelis-Menten models and their activity is match with previous experiment. Based on the Vmax values, the immobilized enzymes showed higher activity than the free enzyme. Cross-linking of immobilized lipase indicate that cross-linking by lower concentration of cross-linker, FIC (immobilized lipase that was incubated for 24 h) gave the highest activity and cross-linking by higher concentration of cross-linker, PIC (immobilized lipase that was incubated for 2 h) gives the highest activity. However, pore size and saturation level influenced their activity.